Natural hazards and public choice : the state and local politics of hazard mitigation - Rossi, Peter H. (Peter Henry), 1921-2006 (Quantitative studies in social relations., 1982)
Natural Hazards and Public Choice: The State and Local Politics of Hazard Mitigation presents a research project that emerged from a concern for estimating the balance of support versus opposition to prospective social policies that aim to reduce the risks of damage or injuries from major natural hazard events via the regulation of land use and establishment of building and occupancy standards in high-risk areas. The volume begins with an overview of the research project and the main findings. Separate chapters describe the study design; assess the views of politically influential people rega.